Rapid Diagnosis of Capnocytophaga Infection Made by Peripheral Blood Smear - Helen Tran; John Park; Paul C. Adamson; Nam K. Ku; Kathryn H. Melamed (Annals of Internal Medicine: Clinical Cases)
Dog bites causing local infection are common but seldom lead to life-threatening complications. We present a case of a 52-year-old woman who presented with septic shock and multiorgan failure after sustaining a dog bite. At presentation, she was in multiorgan failure with a necrotic bite wound on her finger and a petechial rash on her face, arms, and legs. Abdominal imaging revealed asplenia. Her peripheral smear showed rod-like inclusions within neutrophils, consistent with intracellular bacilli. A diagnosis of Capnocytophaga infection was made. She was started on broad-spectrum antibiotics, including piperacillin–tazobactam, and made a full recovery.